Pengaruh Komunikasi Organisasi dan Komitmen Organisasional terhadap Efektivitas Sekolah di SD Godong Grobogan - Retno Susilowati; Soedjono (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2024)
This study aims to examine the influence of organizational communication and organizational commitment on school effectiveness at the elementary level in Godong District, Grobogan Regency. This research employed a quantitative approach using a survey method. The sample consisted of 100 teachers selected through proportional random sampling. Data were collected using a Likert-scale questionnaire, which was tested for validity and reliability. The data were analyzed using multiple linear regression with the help of SPSS software. The results showed that organizational communication had a significant effect on school effectiveness with a significance value of 0.000. Likewise, organizational commitment also had a significant influence, with a significance value of 0.001. Simultaneously, both variables contributed 52.6% to school effectiveness. These findings indicate that effective internal communication and strong teacher commitment are two key factors in improving school quality. Therefore, school principals should develop open communication strategies and empower teachers to be more actively involved in achieving institutional goals.